An analytical and evaluative study of the questions contained in Arabic, Mathematics and French books for the fifth year of primary school According to its type and level of educational goals that you measure according to Bloom’s field of knowledge - Boulkamh, Mohamed; Hiouani, Sabah; Demane Debih, Nour el Houda (Journal of Human Sciences, 2022)
The objective of this study is the analysis of all the questions present in the textbooks of Arabic language, mathematics, French language for the fifth year of primary school, and to determine its type (questions for articles or objective questions), as well as determine the level of educational objectives it measures according to Bloom’s classification for cognitive field objectives. To answer the questions of this study, the researchers used the descriptive method, preparing a content analysis map by which they were able to gather all the questions that appeared in the three textbooks.